Pewarna Alami Tanaman Endemik Dayak untuk Batik Benang Bintik dalam Mendukung Ekowisata Gambut Kalimantan Tengah: Natural Dyes from Dayak Endemic Plants for Benang Bintik Batik to Support Peatland Ecotourism in Central Kalimantan - Setyowati, Erni Dwi Puji; Darmawan, Cahyo Wahyu; Ompusunggu, Dicky Perwira; Girindraswari, Nawung Asmoro (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
The Kereng Bangkirai sub-district, located in the Sebangau Peatland Ecotourism area, has the potential to utilize endemic Dayak plants as natural dyes for the development of dotted batik products. However, its use by the community remains very limited due to a lack of knowledge, innovation, and skills in the production process. The objective of this community service program is to empower the community through training in the production of natural-dye batik, from the introduction of endemic plants and batik techniques to dye extraction from sawang and purun leaves, the mordanting process, and batik dyeing and finishing. The method used is a participatory action research (PAR) approach, which actively involves participants in every stage. The program evaluation instrument uses pre- and post-tests to measure increases in participants' knowledge and skills. The training provided to the Kereng Bangkirai community group received positive responses and support from the village administration. The conclusion of this activity shows an increase in participants' knowledge, skills, and creativity in utilizing natural dyes as an alternative innovation for creative economic products with cultural value that enhance the appeal of peatland ecotourism.